PENGARUH CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSET STUDI KASUS PADA BANK BUMN PERIODE 2019-2023 - Zidane, Rizal; Megawai, Liya (Relawan Jurnal Indonesia, 2024)
his research aims to analyze the influence of capital adequacy ratio on ROA of BUMN Banks for the 2019-2023 period. The method used in this research is a quantitative method with data analysis techniques using simple linear regression. This research uses a probability sampling method, namely a simple random sampling technique or random sampling. The sample for this research is 4 banks which are state-owned banks. This research uses secondary data obtained through financial reports obtained from the OJK (Financial Services Authority) website for the 2019-2023 period. The data analysis method uses SPSS 22 software to obtain simple linear regression analysis results. Based on the research results, it shows that the capital adequacy ratio (CAR) has a significant effect on Return On Assets (ROA).